Pengaruh institusional ownership, firm size dan arus kas operasi terhadap financial distress pada perusahaan food and beverage yang terdaftar di bei tahun 2014-2018 - Mariana Mariana; Anisa Kusumawardani; Rusliansyah Rusliansyah (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2022)
ABSTRACTMariana, 2021. Pengaruh Institusional Ownership, Firm Size dan Arus Kas Operasi Terhadap Financial Distress Pada Perusahaan Food and Beverage Yang Terdaftar di BEI Tahun 2014-2018. Unde The Guidance Dr. Hj. Anisa Kusumawardani, SE., M.Si., CSRS and Rusliansyah, SE., M.Si. This study aims to examine the effect of institutional ownership, firm size and operating cash flow on financial distress in food and beverage companies listed on the BEI. With the number of research observations as much as 125 data from 26 number of Food and Beverage companies in 2014-2018. This study uses analysis tools with multiple linear regression, correlation and determination test and hypothesis testing, namely the t test and model feasibility test (F). The results showed that based on the F test or simultaneously, institutional ownership, firm size and operating cash flow variables had a significant effect on financial distress. Based on the t test or partial institutional ownership has a significant effect on financial distress, firm size has a significant effect on financial distress, and operating cash flow also has a significant effect on financial distress.Â